2011
DOI: 10.3340/jkns.2011.49.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Post-Discectomy Pseudocyst after Endoscopic Lumbar Discectomy

Abstract: Objective : The objectives of this study were to determine the frequency of symptomatic postdiscectomy pseudocyst (PP) after endoscopic discectomy and to compare the results of surgical and conservative management of them. Methods : Initial study participants were 1,503 cases (1,406 patients) receiving endoscopic lumbar discectomy by 23-member board of neurosurgeons from March 2003 to October 2008. All patients' postoperative magnetic resonance imaging (MRI) scans were evaluated. On the postoperative MRI, cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(72 citation statements)
references
References 52 publications
(31 reference statements)
5
67
0
Order By: Relevance
“…The onset of recurrent LDH is expected to be acute; however, the leg pain gradually increased in case 1 ( Table 1). A short duration of symptom improvement may indicate the possibility of recurrent LDH, and the duration of case 1 was within the extent of the previously reported cases (20 vs. 9-118 days) (4,5). Spontaneous regression of the lesion may occur in both pathological conditions (5,14,15).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…The onset of recurrent LDH is expected to be acute; however, the leg pain gradually increased in case 1 ( Table 1). A short duration of symptom improvement may indicate the possibility of recurrent LDH, and the duration of case 1 was within the extent of the previously reported cases (20 vs. 9-118 days) (4,5). Spontaneous regression of the lesion may occur in both pathological conditions (5,14,15).…”
Section: Discussionmentioning
confidence: 54%
“…However, there has been no discussion about differential diagnosis of a simple recurrence of LDH in previous reports (4)(5)(6). We therefore present a case of recurrent LDH resembling symptomatic PDP and real symptomatic PDP, and further discuss the difficulty of the differential diagnosis.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…To the best of the authors' knowledge, only one clinical article and one case report have been published. Kang et al [12] reported an incidence of 1% in a single center study after endoscopic lumbar discectomy (15 lesions in 1,503 cases recorded between March 2003 and October 2008). Young et al published two cases in their case report [30].…”
Section: Discussionmentioning
confidence: 97%
“…Kang et al reported that there was no difference in the treatment outcomes between a surgically managed group and a conservatively managed group [12]. There are a small number of published reports on spontaneous regression of intraspinal extradural cysts [5,7,18,19,26].…”
Section: Differential Diagnosismentioning
confidence: 99%